T-cell receptor and K-deleting recombination excision circles in newborn screening of T- and B-cell defects: review of the literature and future challenges - Marco Chiarini; Cinzia Zanotti; Federico Serana; Alessandra Sottini; Diego Bertoli; Luigi Caimi; Luisa Imberti (SAGE Publishing, 2013)
Since its introduction as a public health programme in the United States in the early 1960s, newborn blood screening (NBS) has evolved from the detection of phenylalanine levels on filter paper to the application of DNA-based technologies to identify T-cell lymphopenia in infants with severe combined immunodeficiency. This latter use of NBS has required the development of an assay for T-cell lymphopenia based on the quantification of T-cell receptor excision circles (TRECs) that could be performed on dried blood spots routinely collected from newborn infants. The TREC-based NBS was developed six years ago, and there have already been 7 successful pilot studies since then. Similarly, efforts are now being made to establish a screen for B-cell defects, in particular agammaglobulinaemia, taking advantage of the introduction of the method for the quantification of K-deleting recombination excision circles (KRECs). A further achievement of NBS could be the simultaneous recognition of T- and B-cell defects using the combined quantification of TRECs and KRECs from Guthrie card blood spots. This approach may help the early identification of infants with T- and B-cell deficiencies so that they can then be referred to specialised paediatric centres, where a precise diagnosis of severe combined immunodeficiency and agammaglobulinaemia can be performed, and where then they can immediately receive specific therapy. Simultaneous TREC and KREC quantification should also allow classification of patients into subgroups and help identify children with less serious primary immunodeficiencies. This would help avoid the opportunistic infections and frequent hospitalisations that result from a late or lack of diagnosis.